CONSTRUCTION OF EFFECTIVE COMPUTING SCHEMES IN MAPLE FOR SOLUTION OF THE PROBLEM OF DETERMINATION OF ULTIMATE STRAIN DURING DIFFICULT STRAIN - Mikhalevich, Vladimir; Dobranyuk, Yuriy; Mikhalevich, Alexey (Scientific Works of Vinnytsia National Technical University, 2015)
There had been considered the problem of determination of ultimate strain of difficult strain which occurs on a free lateral surface at a axial-symmetric compression with variation of friction conditions on end faces. There had been highlighted the key moments of this problem. It had been shown that application of standard commands of system Maple for the sokution of the considered problem is not efficient from the point of view of time spent for carrying out calculations. There had been analysed different approaches to construction of efficient computing schemes. It had been shown that the most efficient is the schema which is based on application of the combined method of chords and tangents. REFERENCES 1. Михалевич В.М. Тензорні моделі накопичення пошкоджень /Вінниця: "УНІВЕРСУМ- Вінниця", 1998 - 195 с. 2. Огородников В. А. Деформируемость и разрушение металлов при пластическом формоизменении. – К.: УМК ВО, 1989. – 152 с. 3. Сивак И. О. Влияние немонотонности нагружения на пластичность при радиальном выдавливании с контурной осадкой // Науковий вісник Національної гірничої академії України – 2001. – с. 47 – 50. 4 .Колмогоров В. Л. Напряжения, деформации, разрушение. – М.: Металлургия, 1970. – 229 с. 5. Сопротивление деформации и пластичность металлов при обработке давлением//Калпин Ю.Г., Перфилов В.И., Петров П.А., Рябов В.А., Филиппов Ю.К. – М.: «МАМИ», 2007. – 118 с. 6. Лебедев А.А., Михалевич В.М. О выборе инвариантов напряженного состояния при решении задач механики материалов//Пробл. прочности. - 2003. - № 3. - С. 5-14. 7. Смирнов-Аляев Г. А. Сопротивление материалов пластическому деформированию. Инженерные методы расчета операций пластической обработки материалов. –М.- Л.: Машгиз, 1961. – 463 с. 8. Мишулин А. А. Михалевич В. М. Тензорно-нелинейная модель накопления повреждений // Обработка металлов давлением. – Свердловск. – 1985. – С. 10-14. 9. Калиткин Н.Н. Численные методы. — М.: Наука, 1978. – 512 с. 10. Maple 9/ Advanced Programming Guide/M.B. Monagan, K.O. Geddes, K.M. Heal, G. Labahn, S.M. Vorkoetter, J. McCarron, P. DeMarco. Canada. Maplesoft, division of Waterloo Maple Inc. 2003. – 443 p.